You have the correct answer. It is choice B) -1/4
=======================================================
Explanation:
This is because we're adding -1/4 to each term to get the next one. In other words, we're subtracting 1/4 from each term to get the next one.
- term2 = term1+(d) = 1/2 + (-1/4) = 1/2 - 1/4 = 2/4 - 1/4 = 1/4
- term3 = term2+(d) = 1/4 + (-1/4) = 1/4 - 1/4 = 0
- term4 = term3+(d) = 0 + (-1/4) = 0 - 1/4 = -1/4
- term5 = term4+(d) = -1/4 + (-1/4) = -2/4 = -1/2
and so on.
----------
To find the common difference, all we have to do is subtract any term from its previous one.
For example:
d = (term2) - (term1)
d = (1/4) - (1/2)
d = (1/4) - (2/4)
d = (1-2)/4
d = -1/4
The order of subtraction matters, so we cannot say d = term1-term2.
Answer:
see attached image
Step-by-step explanation:
F(x) = 2x + 5 is a linear graph because the exponent on x is 1. I tell my students that think of graphs having one less turn/corner that the value of the highest exponent. so since 2x has a exponent of 1, 1-1 =0 so it has no turns or its a straight line.
this has a slope of 2 or 2/1 or up 2 and right 1 from the y intercept which is 5
so mark 5 on the y axis and a from there go up 2 and right 1 and make another point. Join these points and you have your graph
and
g(x) = (x-5)/2 is its inverse and is found:
F(x) = 2x + 5 write it this way y = 2x + 5
now swap the x and y x = 2y - 5
solve for y
x = 2y + 5
- 5 -5
x - 5 = 2y
/2 /2
(x-5)/2 = y
it can be written as y = x/2 - 5/2
and graphed the same way as above with a 1/2 slope and -5/2 y intercept
For this case we have the following quadratic equation:
![-3x ^ 2 + x-4 = 0](https://tex.z-dn.net/?f=-3x%20%5E%202%20%2B%20x-4%20%3D%200)
Where:
![a = -3\\b = 1\\c = -4](https://tex.z-dn.net/?f=a%20%3D%20-3%5C%5Cb%20%3D%201%5C%5Cc%20%3D%20-4)
By definition, the discriminant of a quadratic equation is given by:
![d = b ^ 2-4 (a) (c)](https://tex.z-dn.net/?f=d%20%3D%20b%20%5E%202-4%20%28a%29%20%28c%29)
We have to:
Two different real roots
Two different complex roots
Two equal real roots
Substituting the values we have:
![d = 1 ^ 2-4 (-3) (- 4)\\d = 1-48\\d = -47](https://tex.z-dn.net/?f=d%20%3D%201%20%5E%202-4%20%28-3%29%20%28-%204%29%5C%5Cd%20%3D%201-48%5C%5Cd%20%3D%20-47)
So, we have two different complex roots
Answer:
Two different complex roots
Answer:
the answer is 2× + 3×
Step-by-step explanation:
hope it helps
Low-birthweight i believe.